Successful Deployment of High Flow Nasal Cannula in a Peruvian Pediatric Intensive Care Unit Using Implementation Science—Lessons Learned - Nielsen, Katie R.; Becerra, Rosario; Mallma, Gabriela; Tantaleán da Fieno, José (Frontiers in Pediatrics, 2018)
Acute lower respiratory infections are the leading cause of death outside the neonatal period for children less than 5 years of age. Widespread availability of invasive and non-invasive mechanical ventilation in resource-rich settings has reduced mortality rates; however, these technologies are not always available in many low- and middle-income countries due to the high cost and trained personnel required to implement and sustain their use. High flow nasal cannula is a form of non-invasive respiratory support with growing evidence for use in pediatric respiratory failure. Its simple interface makes utilization in resource-limited settings appealing, although widespread implementation in these settings lags behind resource-rich settings. Implementation science is an emerging field dedicated to closing the know-do gap by incorporating evidence-based interventions into routine care, and its principles have guided the scaling up of many global health interventions. In 2016, we introduced high flow nasal cannula use for respiratory failure in a pediatric intensive care unit in Lima, Peru using implementation science methodology. Here we review our experience in the context of the principles of implementation science to serve as a guide for others considering high flow nasal cannula implementation in resource-limited settings.